PERILAKU KONSUMTIF PEMBELIAN SKINCARE (PERAWATAN KULIT) SECARA ONLINE PADA MAHASISWA JURUSAN TATA RIAS DAN KECANTIKAN FPP UNP - Elvia Reza; Rahmiati Rahmiati (Jurnal Tata Rias dan Kecantikan, 2021)
Thisistudyiaims toi(1) determinei consumptive behavi0r ini buying products because they are interested in the lure of gifts/promotions (2) to determine consumptive behavior in buying products because they are interested in the appearance of the packaging (3) to determine consumptive behavior in using products because of the conformity of the advertised model. This type of research is descriptive research with a quantitative approach. The study population was students majoringi iin Cosmetology and Beauty, Facultyi ofi Tourismi andi Hospitalityi, Padang State University, class of 2017 as many asi 95 people. The sampling technique in this study used a total population sample technique. This typei 0f data is primary. Datai c0llecti0n techniquesii are inii the form of questionnaires or questionnaires distributed through Google Form. The instruments test in this studyi werei validityi andi reliabilityi tests. Thei data analysisi technique utilizes descriptive statistical analysis techniques. Based on the results of the study, it was concluded that the majority of students from the 2017 class of consumptive behavior were in the "Medium" category. Seen from the aspect of buying products because they are attracted to the lure of prizes/promotions as many as 33.20 which reached 32 students (33.6%) in the "medium" category. In the aspect of buying products because they are interested in the appearance of the packaging as many as 23.22 which reached 34 students (35.7%) in the "medium" category. In the aspect of using the product because they are interested in the conformity element of the model, 50.56 advertised which reached 38 students (40%) in the "high" category. So overall the consumptive behavior of purchasing skincare online for students of the Department of Makeup and Beauty, Padang State University is dominant in the "Medium" categ0ry